2021
DOI: 10.1093/infdis/jiab420
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cardiometabolic Diseases in People With and Without Human Immunodeficiency Virus in the United Kingdom: A Population-Based Matched Cohort Study

Abstract: Background Evidence on the risk of cardiovascular disease (CVD) and CVD risk factors in people with human immunodeficiency virus (PWH) is limited. We aimed to identify the risk of composite CVD, individual CVD events, and common risk factors. Methods This was a nationwide, population-based, cohort study comparing adult (≥18 years old) PWH with people without human immunodeficiency virus (HIV) matched on age, sex, ethnicity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Previous studies, typically of long term cohorts, have found increased risk of cardiovascular disease amongst people with HIV. 19 , 20 In our cross-sectional study focusing on 2015, overall probability of ischaemic cardiovascular disease was not elevated, reflecting perhaps the accumulation of awareness about risks, their pro-active management, earlier initiation of HIV therapy, and availability of HIV therapies with fewer metabolic side effects than in the past. We also observed that adults with HIV had a lower probability of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies, typically of long term cohorts, have found increased risk of cardiovascular disease amongst people with HIV. 19 , 20 In our cross-sectional study focusing on 2015, overall probability of ischaemic cardiovascular disease was not elevated, reflecting perhaps the accumulation of awareness about risks, their pro-active management, earlier initiation of HIV therapy, and availability of HIV therapies with fewer metabolic side effects than in the past. We also observed that adults with HIV had a lower probability of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 72%
“…Currently, there is no consensus on the association among HIV infection, ART, and the development of diabetes mellitus (DM) ( 2 ). In several studies ( 4 , 5 ), the association of HIV infection and ART with an increased risk of DM has been suggested with potential mechanisms including chronic inflammation and ART-induced mitochondrial dysfunction ( 6 , 7 ). In contrast, others reached different conclusions ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…This extraordinary change in the circumstances of PLHIV in the UK has not been recognized to date, most likely because deprivation information is not reported in annual public health HIV epidemiology data [2]. Although greater levels of deprivation among PLHIV compared with the general population are widely acknowledged [9], we are not aware of studies demonstrating rising deprivation within the PLHIV population. Coupled with the increased age of the 2015 cohort, this raises the possibility that as PLHIV grow older, and agerelated non-communicable conditions arise, increase or become more severe, employment opportunities and economic status suffer, reflected in higher deprivation levels across the cohort as a whole.…”
Section: Discussionmentioning
confidence: 99%